2009
DOI: 10.1103/physrevb.80.155309
|View full text |Cite
|
Sign up to set email alerts
|

Level-set simulation for the strain-driven sharpening of the island-size distribution during submonolayer heteroepitaxial growth

Abstract: We use an island dynamics model for heteroepitaxial growth to study the narrowing and sharpening of the island-size distribution as a function of the strain in the submonolayer growth regime. Our island dynamics model is coupled to an elastic model that is based on atomistic harmonic interactions. The elastic equations are solved self-consistently at every time step during the simulation for the entire system. This is possible because the numerical time steps in the island dynamics model that is based on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…This shows that the effect of elastic interactions is to both narrow the size distribution and reduce the average size of the islands. This is in agreement with the island dynamics simulation of Ratsch et al [3]. …”
Section: Submonolayer Growthsupporting
confidence: 82%
See 2 more Smart Citations
“…This shows that the effect of elastic interactions is to both narrow the size distribution and reduce the average size of the islands. This is in agreement with the island dynamics simulation of Ratsch et al [3]. …”
Section: Submonolayer Growthsupporting
confidence: 82%
“…This approximation is similar to that used in Ref. [3]. For a procedure somewhat more faithful to the model introduced above, an alternative would be to use the techniques introduced in Ref.…”
Section: Local Energy Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…For heteroepitaxial growth, a lattice mismatch between the substrate and the crystalline form of the deposited material leads to strain buildup, and thus a significant energetic penalty for larger islands inhibiting their growth [40]. A simple strategy to model this behavior is to reduce the rate of the last adatom hop leading to aggregation in the PIM for larger islands by a factor of f(s)  1.…”
Section: Pim For Modified Nucleation and Growth Processesmentioning
confidence: 99%
“…Hereafter, the growth behavior with a growth exponent β > 1/2 is called "superepitaxial growth behavior." In the conventional kinetic theory, QDs are generally considered to grow via uphill mass transport of adatoms driven by the latticemismatch strain [189], which can be implemented well in KMC simulations [190][191][192][193][194]. In their KMC simulation of the heteroepitaxial growth (with the elastic property of the system similar to semiconductors) at a lattice mismatch of 5%, Ratsch et al [192] observed the formation of 3D islands that grow according to the super-epitaxial growth law…”
Section: Super-epitaxial Growthmentioning
confidence: 99%